2015
DOI: 10.1371/journal.pone.0138796
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal and Spatial Invasion Genetics of the Western Corn Rootworm (Coleoptera: Chrysomelidae) in Southern Europe

Abstract: This study describes the genetics of the western corn rootworm (WCR), Diabrotica virgifera virgifera LeConte in southern Europe during the introduction (1996–2001) and establishment/spread (2002–2011) phases of its invasion. The Diabrotica microsatellite core-set was used to perform traditional population genetics analyses. Our results indicated that during the introduction phase genetic diversity and population genetic structure were lower overall as compared to the establishment/spread phase. Unusually high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
1
16
0
1
Order By: Relevance
“…However, this may have been due to the intensive monitoring program in Croatia during the study period [50]. The results confirmed the original finding that allelic richness during the introduction phase was low but consistent throughout all Southern European populations [55]. However, during the establishment and spread phases of the invasion process, allelic richness was higher for all Southern European populations.…”
Section: Genetic Monitoringsupporting
confidence: 80%
See 2 more Smart Citations
“…However, this may have been due to the intensive monitoring program in Croatia during the study period [50]. The results confirmed the original finding that allelic richness during the introduction phase was low but consistent throughout all Southern European populations [55]. However, during the establishment and spread phases of the invasion process, allelic richness was higher for all Southern European populations.…”
Section: Genetic Monitoringsupporting
confidence: 80%
“…Bayesian cluster analysis revealed two genetic clusters that joined the WCR from Croatia and Serbia, but separated them from U.S. populations. These clusters showed that numerous U.S. individuals had both European and U.S. ancestry, which suggests the existence of bidirectional gene flow [55]. Bottlenecks were identified within all Croatian populations sampled in 1996 and 2011 and only two populations in 2009.…”
Section: Genetic Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…For over a century, the WCR was primarily confined to North America with its center of origin believed to be in Central America (Webster 1895, Krysan 1982, Lombaert et al 2018. However, in 1992 it was found in Serbia, and has been spreading through Europe since then (Berger 2001, Miller et al 2005, Wesseler and Fall 2010, Lemic et al 2015, Mrganić et al 2018).…”
Section: Wcr Bio-ecologymentioning
confidence: 99%
“…This insect pest also became a major concern for European countries after it was first found in 1992 close to Surcin International Airport in Belgrade (Berger 2001, Miller et al 2005). Since this first report, WCR has spread to more than 15 countries in Europe and has placed many others at risk of biological invasion (Aragón et al 2010, Wesseler and Fall 2010, Lemic et al 2015, Mrganić et al 2018.…”
Section: Chapter 1 Introduction and Literature Review Introductionmentioning
confidence: 99%